Sanksi Hukum Bagi Pengawas Yayasan yang Lalai dalam Menjalankan Fungsinya Sebagai Organ Yayasan - Bayu Brahmantya, Ida Bagus (Jurusan Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2021)
A foundation is an institution that carries out religious, humanitarian and social activities that are formed by the community or the government. Law Number 16 of 2001 concerning Foundations as later amended by Law Number 28 of 2004 concerning amendments to Law Number 16 of 2001 concerning Foundations which provides certainty of the legal position of foundations as legal entities. Foundations do not have members, but have foundations consisting of coaches, administrators and supervisors who as legal subjects are capable of taking legal actions. The management of foundation assets is open in nature so that proper supervision is required. The Supervisory Organ has the authority to supervise the management of the Foundation by supervising financial reports, activity reports and their achievements which are written by the Management to be ratified in a supervisory meeting. These supervisors must have good faith in carrying out their authority, duties and responsibilities. The method used in this research is normative legal research using a statutory approach. The authority of a Supervisor is regulated in statutory regulations, however, legal sanctions if a Supervisor is negligent in carrying out the function are not completely stated. So that in order to avoid negligence in its function, it is necessary to have strict sanctions to avoid any harm to the Foundation, the state or related parties.